The structure and flexibility of conical HIV-1 capsids determined within intact virions - Mattei, Simone; Glass, Bärbel; Kräusslich, Hans-Georg; Briggs, John A. G. (Science, 2016)
Structural insights into capsid flexibility Viral capsids are protein structures that enclose the genetic material of viruses. Previous structural studies of the HIV-1 capsid have relied on recombinant, cross-linked, or mutant capsid proteins. Mattei et al. now report subnanometer-resolution cryo-electron tomography structures of the HIV-1 capsid from intact virions. These structures confirm the hollow cone shape of the capsid and allow for the specific placement of each individual capsid hexamer and pentamer within the lattice structure. The structures also reveal the flexible nature of the capsid, which likely helps it to accommodate interactions with host cell factors. Science, this issue p. 1434 HIV-1 contains a cone-shaped capsid encasing the viral genome. This capsid is thought to follow fullerene geometry—a curved hexameric lattice of the capsid protein, CA, closed by incorporating 12 CA pentamers. Current models for core structure are based on crystallography of hexameric and cross-linked pentameric CA, electron microscopy of tubular CA arrays, and simulations. Here, we report subnanometer-resolution cryo-electron tomography structures of hexameric and pentameric CA within intact HIV-1 particles. Whereas the hexamer structure is compatible with crystallography studies, the pentamer forms using different interfaces. Determining multiple structures revealed how CA flexes to form the variably curved core shell. We show that HIV-1 CA assembles both aberrant and perfect fullerene cones, supporting models in which conical cores assemble de novo after maturation. High-resolution structures of the capsid from intact HIV-1 virions suggest that it forms after virus maturation. High-resolution structures of the capsid from intact HIV-1 virions suggest that it forms after virus maturation.